Abdulla Avlani, The Famous Educator Adib and Dramatist, in the Context of Today's Times - Rahimjonova Dilfuza (Web of Journals Publishing, 2023)
One of the largest manifestations of Uzbek literature, studying the work of Abdullah Avloniy, is literally the responsibility of every younger generation. Indeed, studying and studying the leading pedagogical views and ideas in his writings will allow not only the learning process to be heated and improve the quality of education. During this article, we will try to get acquainted with the main ideas in the works of Abdullah Avloniy.